2011
DOI: 10.4236/ijg.2011.24054
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Interpretation of the Cameroon Mountain (West Central Africa) Based on the New and Existing Data

Abstract: A new gravity survey of the Mount Cameroon area has enabled the definition of four major gravimetric domains, which coincide with the recognized structural units. In order to determine the nature of superficial and deep structures in this mountainous zone, new gravity data have been processed. These new gravity data was integrated to existing gravity data to propose the new complete Bouguer anomaly map of the region, and then to show major characteristics of the Bouguer gravity of this area. The interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Mount Cameroon is an inaccessible area to measure gravity data because of its rugged terrain. Many geophysical investigations with new gravity data are being carried out around this area to improve knowledge of the nature of shallow and deep structures, the orthometric height of Mount Cameroon, and the depth of various geological features (Kenfack et al, 2011; Kamguia et al, 2015; Nguiya et al, 2019). Despite better results, improvements are still to be made in our knowledge of this mountainous area.…”
Section: Resultsmentioning
confidence: 99%
“…Mount Cameroon is an inaccessible area to measure gravity data because of its rugged terrain. Many geophysical investigations with new gravity data are being carried out around this area to improve knowledge of the nature of shallow and deep structures, the orthometric height of Mount Cameroon, and the depth of various geological features (Kenfack et al, 2011; Kamguia et al, 2015; Nguiya et al, 2019). Despite better results, improvements are still to be made in our knowledge of this mountainous area.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, with a tolerance value taken equal to 0.3 km, the depth of the roof of G5 can vary from 0 to 0.7 km, which is consistent with the value of about 0.6 km found by spectral analysis; It can also be stated that a continuous variation of the base depth from 0.5 km to 3.7 km would correspond to a structure that creates an anomaly equal to that of a body with a base at a constant depth of about 3.8 km and another interface at a constant depth of about 2 km that is due to a change in the lateral extent of the intrusive body. In Figure 13 The density contrast values obtained by inversion (0.12, 0.13 and 0.18 g/cm 3 ) indicate that the intrusive bodies G5, G8 and G11 are denser than the surrounding rock, which leads them to create positive anomalies, invisible signs of infiltration of magmatic rocks at the surface (Kenfack et al, 2011). We also note that the superposition map of the residual of order 7 with the intrusive bodies (Figure 7) shows that many of these intrusive structures have created positive anomalies.…”
Section: Discussionmentioning
confidence: 98%
“…These include studies across the country, such as the work of Poudjom Djomani et al (1995) with gravity data and those of Tokam et al (2010) using seismic data. On a smaller scale, we can cite the work of Ateba et al (2009) and that of Kenfack et al (2011). The studies of Poudjom Djomani et al (1995) were carried out in a regional framework, extended over several hundreds of kilometers, largely with evidence of deep structural contrasts, located in the upper mantle.…”
Section: Introductionmentioning
confidence: 99%
“…The meaning attributed to gravity anomaly do not take into account the effect of gravitational density contrast due to the structure of the crust. The work of Kenfack et al (2011) established the new gravity map and provides support for any interpretation of gravity anomalies in the region. Ateba et al (2009), using the seismic method showed eruptive sites and directions of volcanic lava flows during the eruption of 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation